Peran Manajemen Pendidikan Islam dalam Pengembangan Lembaga Pendidikan di MAN 4 Bantul Yogyakarta (Lembaga Pengembangan Kinerja Dosen, 2025)
This journal discusses the role of Islamic education management in educational institutions and how to develop them. This research uses qualitative methods, with data collection through observation, interviews, and in-depth literature review. The main findings of this study involve various important components in educational management, including curriculum management, human resources, infrastructure, financing, public relations, and special services. One of the educational institutions analyzed, MAN 4 Bantul, identified four main points in the development of educational institutions. First, the use of the independent curriculum to provide freedom in the learning process; second, the application of Islamic character to shape students' morals; third, increasing individual worship and faith to always be grateful according to Islamic teachings; and fourth, developing branding through information management in the field of public relations. In addition, MAN 4 Bantul also improves the quality of human resources through learning innovation workshops for educators. The results of this study indicate that Islamic education management integrated with religious principles can create a more effective, relevant, and sustainable learning environment, as well as strengthen the competitiveness of educational institutions in the digital era.